2018
DOI: 10.1039/c7nr07776a
|View full text |Cite
|
Sign up to set email alerts
|

Rb+ cations enable the change of luminescence properties in perovskite (RbxCs1−xPbBr3) quantum dots

Abstract: All-inorganic metal halide perovskites of the formulation ABX (where A is Cs, B is commonly Pb, and X is a halide, X = Cl, Br, I) have been studied intensively for their unique properties. Most of the current studies focus on halogen exchange to modify the luminescence band gap. Herein we demonstrate a new avenue for changing the band gap of halide perovskites by designing mixed-monovalent cation perovskite-based colloidal quantum dot materials. We have synthesized monodisperse colloidal quantum dots of all-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 35 publications
3
46
0
1
Order By: Relevance
“…We introduce Rb + into CsPbBr 3 nanocrystals during synthesis to enlarge the bandgap. Rb‐doping in perovskite QDs and quasi‐2D thin films have been previously reported, where it was found to blue‐shift the absorption and PL properties …”
Section: Peled Electroluminescence Performance Metricsmentioning
confidence: 86%
See 1 more Smart Citation
“…We introduce Rb + into CsPbBr 3 nanocrystals during synthesis to enlarge the bandgap. Rb‐doping in perovskite QDs and quasi‐2D thin films have been previously reported, where it was found to blue‐shift the absorption and PL properties …”
Section: Peled Electroluminescence Performance Metricsmentioning
confidence: 86%
“…We used these metrics to estimate the limit to Rb + doping of CsPbBr 3 ( t = 0.92) with Rb + to increase the bandgap. Finite Rb + incorporation results in further tilting of the PbX 6 octahedra, reducing the overall orbital overlap and hence opening up the bandgap of CsPbBr 3 while simultaneously reducing the tolerance factor . However, it has been reported that an upper bound of 70% Rb + exists in a mixed cation perovskite QD, as pure RbPbBr 3 does not exist under ambient conditions …”
Section: Peled Electroluminescence Performance Metricsmentioning
confidence: 99%
“…[23][24][25][26] Rb x Cs 1Àx PbBr 3 perovskite quantum dots were found to exhibit high quantum yield (93 %), narrower photoluminescence (PL) emission linewidth (18-27 nm), and excellent wide color gamut coverage. [27][28][29][30][31] However,all-inorganic perovskite RbPbBr 3 structures have still not been realized. Theoretical stability,a si ndicated by the tolerance factor t,s hould be considered carefully for the realization of the all-inorganic RbPbBr 3 perovskite.T he tolerance factor of RbPbBr 3 is about 0.78 (the effective ionic radii of Rb + ,Pb 2+ ,and Br À are 1.61, 1.19, and 1.96 ,r espectively).…”
mentioning
confidence: 99%
“…After the heat treatment, multiple peaks merge into a wide peak. To prove that Eu 3+ was successfully mixed into the quantum dots, the XRD patterns (Figure F) are then investigated, compared with the undoped quantum dots, the 2θ value of Eu 3+ ‐doped samples shift to larger angle, this is because the Eu 3+ ionic radius is smaller than that of Pb 2+ (98 pm for Pb 2+ , 94.7 pm for Eu 3+ ), crystal lattice constriction occurs, resulting in the diffraction peak shifting to the right in the XRD patterns when Pb 2+ is replaced by Eu 3+ , Which is consistent with the results reported by Wu et al When the mole concentrations of Eu 3+ ions increase continously, the number of Eu‐doped CsPbBr 1.5 I 1.5 QDs peaks disappeared in XRD patterns, which indicates that the ordered perovskite structure has been destroyed. The absorption spectra are displayed in Figure G, with the intervene of Eu 3+ ions, the absorption value of quantum dots reduced in different extents.…”
Section: Resultsmentioning
confidence: 99%